Building the Ecosystem for Social Entrepreneurship: University Social Enterprise Cases in Singapore. (November 2019) - Cheah, Sarah; Ho, Yuen-Ping
There has been limited study on the role of the startup ecosystem in social entrepreneurship. This article addresses the gap by applying a theoretical framework of startup ecosystem to two social enterprises originating from a Singapore university, examining how they engage with stakeholders to create social impact. WateRoam Pte Ltd is a water innovation startup that deploys cost-effective water filtration solutions to rural communities and disaster-hit locations. Tware is a wearable technology startup with a range of therapeutic products for individuals with autism, stress or anxiety. The two cases provide insights on the ecosystem for social ventures in Singapore. The Finance domain is identified as a potential area of improvement, as there is uncertainty on the appropriate growth trajectory for funding. University incubation and mentor networks are found to be pivotal in extending the Markets domain. Finally, this study highlights the Supports domain in the form of university R&D facilities and accelerator programmes that have been instrumental in strengthening connections. Extending beyond the university context, it is evident that infrastructural resources in the ecosystem are crucial. Policymakers may draw on the experience of countries, like Israel, which have successfully built such support facilities to nurture innovation-based social enterprises.